(untitled) (Bangladesh Pharmaceutical Journal, 2019)
The genus Acacia is a pioneering source of diversified chemical compounds. The purpose of this review is to compile of the phytochemicals from few species of Acacia. A total ten species of Acacia were studied and seventy six (1-76) phytoconstituents, including their chemical structures are reported in this review. The highest number of chemical compounds has been reported from Acacia nilotica. Bangladesh Pharmaceutical Journal 22(2): 235-242, 2019